POSITION-RELATED ERUPTION DISORDER WITH ECTOPIC ERUPTION OF MAXILLARY CENTRAL INCISOR - case report - Srbinoska, Daniela; Trpevska, Vesna; Simjanovska, Simona; Cadikovksa, Elizabeta (Journal of Morphological Sciences, 2023)
Differential growth is the basis for normal and harmonious completion of various physiologic processes including the eruption of the teeth. The disturbance of the differential growth pattern of tooth eruption can revealed as ectopic tooth eruption or tooth impaction. Ectopic teeth are similar to impacted teeth and can be both ectopic and impacted. The difference is that ectopic teeth does not follow its usual course and erupt somewhere they shouldnâ€™t (referred to as an â€˜abnormal eruption path), whereas impacted teeth may be on course to erupt in the right spot, but are simply not able to erupt. The occurrence of ectopic eruption is most commonly associated with maxillary incisors. This condition compromises facial aesthetics, phonation as well as masticatory function. Therefore, an early and accurate diagnosis supported by clinical and radiological examinations, such as OPG X-ray is essential in manner to avoid complications and failures. Appropriate orthodontic treatment can prevent a more complicated malocclusion. The purpose of following case report is presenting an orthodontic treatment in case of early mixed dentition with ectopically erupted maxillary right central incisor. The treatment plan involved utilization of Schwartz removable appliance designed to expand the upper jaw. The aim was to obtain more space for the central incisor in the first phase and positioning the tooth into the dental arch with good bone and periodontal support in the second phase. The patient had improvement in the upper lip support and the smile aesthetics. The treatment is ongoing. Keywords : eruption disturbances, ectopic tooth eruption, impacted teeth, removable orthodontic appliance.   https://doi.org/10.55302/JMS2361136s